EFEKTIVITAS PENYALURAN ZAKAT TERHADAP PENURUNAN ANGKA KEMISKINAN (STUDI PENELITIAN DI BAITUL MAL KOTA LHOKSEUMAWE) - Cut Afrida; Armiadi Musa; Muhammad Arifin (JIM : Journal Of International Management, 2025)
This study aims to examine the effectiveness of zakat distribution in reducing poverty levels in Lhokseumawe City through programs implemented by the Baitul Mal of Lhokseumawe City. Although zakat has significant potential as a poverty alleviation instrument, several challenges remain in practice, including suboptimal distribution, inaccurate identification of eligible beneficiaries (mustahik), and limited available funds. This research employs a descriptive qualitative method, with data collected through field observations, in-depth interviews with Baitul Mal officials, and documentation studies based on institutional reports and data from the Central Bureau of Statistics of Lhokseumawe City. The findings indicate that zakat distribution programs have provided tangible benefits to mustahik, particularly through productive business capital assistance and skills training initiatives. However, the overall effectiveness of these programs still requires improvement. Enhancing data accuracy, implementing more structured distribution strategies, and strengthening continuous monitoring and evaluation systems are essential to achieving optimal and sustainable long-term impacts on poverty reduction in Lhokseumawe City.